Recommendations on the geometrical imperfections definition for the resistance of I-sections. (November 2019) - Gérard, Lucile; Li, Liya; Kettler, Markus; Boissonnade, Nicolas
Abstract: The resistance and design of steel sections such as I and H-shapes usually depends in great extents on their ability to resist buckling, as a result of high width-to-thickness b / t ratios in the plates constituents. Consequently, these sections remain quite sensitive to imperfections. Information on imperfections, a key data for F.E. simulations, is however quite lacking in design standards, either for material imperfections or for geometrical imperfections. Accordingly, an extensive numerical study on hot-rolled and welded I and H-sections was carried out with the aim of providing reliable and efficient recommendations for the F.E. modelling of initial geometrical imperfections. Several sets of imperfections were investigated including the use of (i) sine-shape functions and of (ii) the 1st buckling mode shape. Reliable recommendations based on modification of nodes coordinates by means of sine-shape functions could be proposed afterwards.